Comparative analysis of anthelmintic treatments: impact on liver biomarkers and clinical recovery in sheep with fasciolosis - Gedefaw, Tameru; Mebratu, Atsede Solomon; Dagnachew, Shimels; Fenta, Melkie Dagnaw (Frontiers in Veterinary Science, 2025)
BackgroundLiver fluke infections (fasciolosis) in sheep in Ethiopia result in significant economic losses, recently estimated at around $3,700 (185,232 ETH Birr) per year. Despite the widely use of Triclabendazole (TCBZ), Tetraclozan (TETRA), and Albendazole (ALBE) for treating fasciolosis, their effectiveness remains a significant concern. This study aimed to compare the efficacy of TCBZ, TETRA, and ALBE in treating ovine fasciolosis, with a focus on their effects on both the parasitic infection and associated biochemical parameters. Given the substantial economic burden of liver fluke in Ethiopia, identifying the most effective treatment options is essential to reducing both the health impact on livestock and the economic losses to farmers.MethodsA field trial was conducted from May to November 2023 on 45 naturally infected sheep, divided into three groups: Group I received TCBZ, Group II TETRA, and Group III ALBE, with TCBZ as the positive control. Fecal and serum samples were collected on days 0, 7, 14, and 21 post-treatment. A fecal egg count reduction test (FECRT) and biochemical analysis were performed.ResultsIn our study, TCBZ was the most effective anthelmintic (97.8%), followed by TETRA (96.6%), and ALBE (84%). Biochemical parameters, particularly liver enzymes (AST, ALT, ALP, GGT) and protein levels, showed significant improvement across all groups over 21 days (p < 0.05), with enzyme levels normalizing by day 21 and protein levels by days 14-21. Albendazole significantly (p < 0.05) outperformed Tetraclozan and Triclabendazole in both biochemical parameters and eggs per gram count (EPG), with no significant difference between Tetraclozan and Triclabendazole (p > 0.05). Albendazole proved most effective for liver recovery and normalization of biochemical markers over the treatment period (p = 0.00). Among 15 Fasciola-infected animals, baseline signs included diarrhea (53%), pale mucous membranes (100%), bottle jaw (60%), and depression (80%). Post-Tetraclozan treatment, all symptoms reduced significantly over 21 days (p < 0.05). In the Albendazole group, symptoms decreased progressively, with diarrhoea, pale mucous membranes, bottle jaw, and depression notably reduced by days 7, 14, and 21.ConclusionTCBZ and TETRA were highly effective against ovine fasciolosis, with TETRA recommended if TCBZ is unavailable. Biochemical parameters are key biomarkers for liver damage and selecting effective anthelmintic drugs.